An efficient continuous quorum quenching feed to mitigate membrane biofouling in membrane bioreactors: Strain 1A1 (extracellular) versus strain BH4 (intracellular). (April 2023) - Kim, In; Jang, Jun-U; Park, Hyeyeon; Park, Jeongmi; Oh, Hyun-Suk; Lee, Seonki; Choo, Kwang-Ho; Park, Pyung-Kyu; Lee, Kibaek
Abstract: Biofouling of the membrane surface of the filtration module remains a major challenge. Various types of quorum quenching (QQ) media have been studied to mitigate membrane biofouling in membrane bioreactors (MBRs). However, a physical fouling issue occurred due to trapping of QQ media in the hollow-fiber module, and this was considered to be one of the reasons for the difficulty in applying QQ-MBRs worldwide. In this study, we continuously supplied the QQ effect without directly injecting a fluidized QQ medium into the membrane tank of the MBRs. The traits of the QQ strain play crucial roles in continuous QQ feeding systems. Comparison of Pseudomonas sp. 1A1 (exo, extracellular) and Rhodococcus sp. BH4 (endo, intracellular) revealed that the exo-type of strain 1A1 is suitable for continuous QQ feeding. The increase in transmembrane pressure (TMP) in the Ex-QQ MBR was mitigated by about 1.7 times compared to that in the Ex-Vacant MBR, and at the same TMP and operating time, the EPS concentration in the Ex-QQ MBR was successfully reduced by 50.1 % and 13.8 %, respectively. PICRUSt was used to predict the functional genes related to biofilm formation and transporter gene-related EPS between Ex-Vacant and Ex-QQ MBR, and the results revealed that the Ex-Vacant MBR had notably greater relative abundance of genes related to biofilm formation and EPS production than those of the Ex-QQ MBR. Thus, QQ via strain 1A1 in the Ex-QQ MBR could reduce membrane biofouling by lowering biofilm formation and EPS production genes in microbial communities. Graphical abstract: Unlabelled Image Highlights: External QQ chamber develops for continuous feeding QQ effect to control biofouling External QQ feeding via Ex-QQ chamber no longer causes physical fouling by QQ media. Strain 1A1 (exo) is more suitable for continuous QQ feeding than strain BH4 (endo). Continuously fed QQ effect is promising for sustainable MBR applications.